Improvement of mood and sleep alterations in posttraumatic stress disorder patients by eye movement desensitization and reprocessing - Raboni, Mara R.; Alonso, Fabiana F. D.; Tufik, Sergio; Suchecki, Deborah (Frontiers in Behavioral Neuroscience, 2014)
Posttraumatic stress disorder (PTSD) patients exhibit depressive and anxiety symptoms, in addition to nightmares, which interfere with sleep continuity. Pharmacologic treatment of these sleep problems improves PTSD symptoms, but very few studies have used psychotherapeutic interventions to treat PTSD and examined their effects on sleep quality. Therefore, in the present study, we sought to investigate the effects of Eye Movement Desensitization Reprocessing therapy on indices of mood, anxiety, subjective, and objective sleep. The sample was composed of 11 healthy controls and 13 PTSD patients that were victims of assault and/or kidnapping. All participants were assessed before, and 1 day after, the end of treatment for depressive and anxiety profile, general well-being and subjective sleep by filling out specific questionnaires. In addition, objective sleep patterns were evaluated by polysomnographic recording. Healthy volunteers were submitted to the therapy for three weekly sessions, whereas PTSD patients underwent five sessions, on average. Before treatment, PTSD patients exhibited high levels of anxiety and depression, poor quality of life and poor sleep, assessed both subjectively and objectively; the latter was reflected by increased time of waking after sleep onset. After completion of treatment, patients exhibited improvement in depression and anxiety symptoms, and in quality of life; with indices that were no longer different from control volunteers. Moreover, these patients showed more consolidated sleep, with reduction of time spent awake after sleep onset. In conclusion, Eye Movement Desensitization and Reprocessing was an effective treatment of PTSD patients and improved the associated sleep and psychological symptoms.